Sustainability of The Agroforestry Management System on Perhutani Forest Land in Malang Regency, East Java, Indonesia - Mujaddid, Muhammad Ashri; Suhartini, Suhartini; Asmara, Rosihan (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
The Forest Management Program with the Community (PHBM) is a program that provides an opportunity for communities living around forests to participate in managing forests by planting seasonal crops with the concept of agroforestry. However, there are any threats to agricultural sustainability in the form of critical land, pest attacks, institutional functions that are not running well, and non-optimal usage of technology. This study aims to examine the sustainability of farming on Perhutani land which is assessed from the five dimensions of sustainability: ecology, economic, social, institutional, and technology. The data collected by distribute the questionnaires to respondents. Respondents in consist of 67 people in total who divided into 60 farmers, and seven stakeholders. Data analysis used the MDS (Multidimensional Scaling) method and leverage analysis to see the attributes that affect sustainability. The results of the study have a sustainability index value of 53.778%, it is categorized as Sufficiently Sustainable in terms of institutional dimensions about (67.119%), ecology dimensions (61.119%), and economic dimensions (58.332%). Meanwhile, the social dimension (44.597%) and the technology dimension (37.727%) are less sustainable. The leverage analysis shows 25 sensitive attributes that affect the sustainability of farming on Perhutani's land in each dimension.